2016
DOI: 10.1371/journal.pone.0163965
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of HPV Genotypes among HIV Positive Women in Kenya: A Systematic Review and Meta-Analysis

Abstract: BackgroundThere is a scarcity of data on the distribution of human papillomavirus (HPV) genotypes in the HIV positive population and in invasive cervical cancer (ICC) in Kenya. This may be different from genotypes found in abnormal cytology. Yet, with the advent of preventive HPV vaccines that target HPV 16 and 18, and the nonavalent vaccine targeting 90% of all ICC cases, such HPV genotype distribution data are indispensable for predicting the impact of vaccination and HPV screening on prevention. Even with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 50 publications
7
55
6
Order By: Relevance
“…Our meta-analysis demonstrated a high burden of HR-HPV genotypes with 64% (95%CI: 50%–77%) in a general HIV population in Kenya ( Menon et al, 2016a ), significantly higher than a recent meta-analysis on pooled HPV prevalence in the general female population in eastern Africa (42.2%) ( Ogembo et al, 2015 ). This finding suggests that a compromised immune system may be a risk factor for HR-HPV acquisition.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations
“…Our meta-analysis demonstrated a high burden of HR-HPV genotypes with 64% (95%CI: 50%–77%) in a general HIV population in Kenya ( Menon et al, 2016a ), significantly higher than a recent meta-analysis on pooled HPV prevalence in the general female population in eastern Africa (42.2%) ( Ogembo et al, 2015 ). This finding suggests that a compromised immune system may be a risk factor for HR-HPV acquisition.…”
Section: Resultscontrasting
confidence: 67%
“…A borderline statistically significant difference in our recent meta-analysis in Kenya between pooled estimates of HR-HPV genotypes in FSW and the general HIV population suggested that a cost-effective approach for cervical cancer prevention may warrant a triage based on this risk factor ( Menon et al, 2016a ). Moreover, our study found that of the 192 HIV-infected FSW, 27.1% (95% CI: 20.9–34.0%) had abnormal cytology ( Menon et al, 2017b ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The prevalence of HPV varied according to geographical location, but was generally at least twofold higher among WLWH compared to HIV-negative women: 62% vs. 24% in sub-Saharan Africa, 30% vs. 14% in Europe, and 30% vs. 5% in North America [6,7]. A metaanalysis among WLWH from Kenya estimated the prevalence of hrHPVs among WLWH to be as high as 64%, with HPV16/18 accounting for 61% of invasive cervical carcinoma (ICC) cases [8]. Similarly, the most recent meta-analysis of data from highincome Western countries showed a 46% vs. 29% prevalence of cervical hrHPV infection in WLWH and in the general US female population, respectively [9] (Figure 1).…”
Section: Cervixmentioning
confidence: 99%